Resveratrol Inhibits Growth of Experimental Abdominal Aortic Aneurysm Associated With Upregulation of Angiotensin-Converting Enzyme 2. Issue 11 (November 2017) - Moran, Corey S.; Biros, Erik; Krishna, Smriti M.; Wang, Yutang; Tikellis, Chris; Morton, Susan K.; Moxon, Joseph V.; Cooper, Mark E.; Norman, Paul E.; Burrell, Louise M.; Thomas, Merlin C.; Golledge, Jonathan
Abstract : Objective—: Recent evidence suggests an important role for angiotensin-converting enzyme 2 (ACE2) in limiting abdominal aortic aneurysm (AAA). This study examined the effect of ACE2 deficiency on AAA development and the efficacy of resveratrol to upregulate ACE2 in experimental AAA. Approach and Results—: Ace2 deletion in apolipoprotein-deficient mice ( ApoE −/− Ace2 −/y ) resulted in increased aortic diameter and spontaneous aneurysm of the suprarenal aorta associated with increased expression of inflammation and proteolytic enzyme markers. In humans, serum ACE2 activity was negatively associated with AAA diagnosis. ACE2 expression was lower in infrarenal biopsies of patients with AAA than organ donors. AAA was more severe in ApoE −/− Ace2 −/y mice compared with controls in 2 experimental models. Resveratrol (0.05/100-g chow) inhibited growth of pre-established AAAs in ApoE −/− mice fed high-fat chow and infused with angiotensin II continuously for 56 days. Reduced suprarenal aorta dilatation in mice receiving resveratrol was associated with elevated serum ACE2 and increased suprarenal aorta tissue levels of ACE2 and sirtuin 1 activity. In addition, the relative phosphorylation of Akt and ERK (extracellular signal-regulated kinase) 1/2 within suprarenal aorta tissue and gene expression for nuclear factor of kappa light polypeptide gene enhancer in B cells 1, angiotensin type-1 receptor, and metallopeptidase 2 and 9 were significantly reduced. Upregulation of ACE2 in human aortic smooth muscle cells by resveratrol in vitro was sirtuin 1-dependent. Conclusions—: This study provides experimental evidence of an important role for ACE2 in limiting AAA development and growth. Resveratrol upregulated ACE2 and inhibited AAA growth in a mouse model. Abstract : Supplemental Digital Content is available in the text.